La religione come "tecnica": Riflessioni storico-religiose sull'efficacia di alcune pratiche psicocorporee che utilizzano la dissociazione psichica in situazione rituale - Mancini, Silvia (Studi e materiali di storia delle religioni, 2018)
This paper deals with one of the questions of anthropology and history of religions which have been most discussed throughout the 20th century: that of the so-called 'symbolic efficacy'-- in other words, of the concrete and objectifiable effects brought about by the ritual action. The approach tendered here suggests a direction that breaks with the interpretations which, while neglecting the factual effects of rite, justify its efficacy by resorting to 'belief' -- namely, to the order of social representations on which the said efficiency is supposed to be based. When studying certain symbolic formations unfamiliar to hegemonic theologies and modern philosophies (both based on the primacy of belief over practices), the modus operandi of the actors -- mobilization of the body, and plastic resources of the psyche -- should be taken into account, to the detriment of 'representations' and systematic ideologies. Such a methodological choice involves an opening to new theoretical and disciplinary contributions, mostly to those of constructivism, and pragmatics, but also of modern hypnosis as re-founded by Milton Erickson. The methodological position presented here has an obvious advantage: it facilitates the definitive emancipation from the history of religions, from this latter's ultimate remnants of theological and essentialist thought, which are still weighing upon the methods and the objects of that discipline. (English)